Genome anatomy of the gastrointestinal pathogen, Vibrio parahaemolyticus of crustacean origin - Tiruvayipati, S.A.; Bhassu, S.; Kumar, N.; Baddham, R.; Sabiha, S.; Anil Kumar, G.; Thong, Kwai Lin; Niyaz, A. (BioMed Central, 2013)
Vibrio parahaemolyticus, an important human pathogen, is associated with gastroenteritis and transmitted through partially cooked seafood. It has become a major concern in the production and trade of marine food products. The prevalence of potentially virulent and pathogenic V. parahaemolyticus in raw seafood is of public health significance. Here we describe the genome sequence of a V. parahaemolyticus isolate of crustacean origin which was cultured from prawns in 2008 in Selangor, Malaysia (isolate PCV08-7). The next generation sequencing and analysis revealed that the genome of isolate PCV08-7 has closest similarity to that of V. parahaemolyticus RIMD2210633. However, there are certain unique features of the PCV08-7 genome such as the absence of TDH-related hemolysin (TRH), and the presence of HU-alpha insertion. The genome of isolate PCV08-7 encodes a thermostable direct hemolysin (TDH), an important virulence factor that classifies PCV08-7 isolate to be a serovariant of O3:K6 strain. Apart from these, we observed that there is certain pattern of genetic rearrangements that makes V. parahaemolyticus PCV08-7 a non-pandemic clone. We present detailed genome statistics and important genetic features of this bacterium and discuss how its survival, adaptation and virulence in marine and terrestrial hosts can be understood through the genomic blueprint and that the availability of genome sequence entailing this important Malaysian isolate would likely enhance our understanding of the epidemiology, evolution and transmission of foodborne Vibrios in Malaysia and elsewhere.